Représentation particulière d'un dieu du vent dans la Pannonie romaine - Szabó, Ádám (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
A fragment of a grave stele was found in the area of Pannonia inferior, Campona (Nagytétény, Budapest, Distr. III). A wind god depicted alone, facing forward can be seen on its ornamentation between two lions. This type of representation of one wind god is considered rare. Wind gods in the Roman sepulcral symbolic probably represent the vertical plane of the afterworld, while the frequently occuring sea creatures represent the horizontal plane within the known world (Cosmos).